The Effectiveness of Information Services Using Problem Based Learning Approach to Reduce Academic Procrastination of Counseling Students - Anna Ayu Herawati; Arsyadani Mishbahuddin; Mellyta Uliyadari; Adif Jawadi Saputra (IJORER : International Journal of Recent Educational Research, 2021)
This research is motivated by the very fact that there are still students who procrastinate, especially academic assignments, during this case, called the wife of student academic procrastination. Efforts made in reducing the extent of student academic procrastination are information services employing a problem-based learning model. This research aims to look at the effectiveness of data services using problem-based learning models to scale back student academic procrastination. This research uses quantitative methods. the sort of this research is Quasi Experiment with One Group Pretest-Posttest Design. the themes of this research were counseling students at the University of Bengkulu. The research instrument used was a Likert scale model. The results showed that information services using effective problem-based learning models to scale back student academic procrastination. The implication of the results of this study is that it are often used as input in creating guidance and counseling service programs, especially in information services using problem-based learning models to scale back student academic procrastination.